Trends and Risk Factors in Occupational Accidents Due to Electrical Contact in Peru (2010–2024): A Correlational Analysis and Prevention Strategies Based on International Standards (Medicina y Seguridad del Trabajo, 2025)
Introduction: Occupational accidents involving electrical contact are a significant cause of morbidity and mortality in industrial settings. This study analyzes their incidence in Peru between 2010 and 2024, assessing risk factors and proposing preventive strategies based on international regulations.Method: A quantitative, non-experimental, correlational study was conducted based on the analysis of 168 statistical bulletins from the Ministry of Labor and Employment Promotion. Shapiro-Wilk normality tests and Spearman correlation analysis were used to assess the relationship between variables such as total workplace accidents, electrical accidents, fatal accidents, and hazardous incidents.Results: A strong correlation was found between total occupational accidents and electrical accidents (r=0.835; p
Keywords: occupational safety; electrical accidents; risk prevention; hazardous incidents